Inconsistencies and Adjustments in Language Policy: Evidence from the Linguistic Landscape - Selim Ben-Said (TRANSBAHASA, 2021)
Taking effect immediately following Tunisia’s independence, Arabization has achieved mixed results with Arabic institutionally empowered but still competing with French. In fact, when examining the linguistic landscape, this monolingual policy is flouted both in terms of the bilingual Arabic-French Street signage but also challenged by people’s preferences. This paper examines inconsistencies between Arabic as the ‘language of the state’ (government-decreed), and the omnipresence of other ‘languages in the state’ (observed in representation and practice) in Tunisia. Street signage artefacts and attitudinal data also illustrate how language policies are responded to and experienced by Tunisians. Data consists of different types of private inscriptions and public signs, governmental decrees, as well as attitudinal surveys and interviews. The juxtaposition of urban signs with the official policy on multilingualism provides an illustrative account of the complexities of the linguistic situation in Tunisia, which blends top-down advocacies of Arabization, ambivalent attitudes to Arabic-French Bilingualism, as well as a growing interest in English as the emergent language of globalization.